(untitled) (Global Journal of Human-Social Science, 2024)
Tax evasion and the presence of fraud in tax administration are phenomena which hit developing countries hardest this can be witnessed from different developing countries indicates that half or more of the taxes that should be collected cannot be traced by the government treasuries due to corruption and tax evasion The general objective of the study was to assess factors responsible for tax evasion among small enterprise owners in Tanzania Specifically the study determined ways used by small enterprises owners in evading tax examined the perception of retail shops owners on tax compliance and in the study area and examined factors influencing tax evasion among small enterprises owners in the study area